A graphene-based solid acid catalyst, preparation method and application thereof, and method for treating flue gas containing CO2

By using graphene-based solid acid catalysts, the problems of high desorption energy consumption and strong corrosiveness in the existing CO2 capture technology are solved, and the reduction of CO2 desorption temperature and optimization of energy consumption are achieved.

CN118403656BActive Publication Date: 2025-02-21XIAMEN SIYAN NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410519162.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-28
Publication Date
2025-02-21
Estimated Expiration
2044-04-28

AI Technical Summary

Technical Problem

In the existing CO2 capture technology, the desorption energy consumption is high and the corrosion is strong, which limits the widespread application of the technology.

Method used

A graphene-based solid acid catalyst is used, which is supported on a molecular sieve support by graphene oxide, WO3 and TiO2 as active components, and is used for desorption of CO2 amine-rich liquid.

Benefits of technology

The CO2 desorption temperature is significantly reduced to 60-90°C, the desorption energy consumption is reduced by more than 30%, and corrosion and pressure are reduced, thereby reducing the material and cost of the desorption tower.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118403656B_ABST
    Figure CN118403656B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of CO2 capture technology, and specifically relates to a graphene-based solid acid catalyst, a preparation method and application thereof, and a method for treating CO2 flue gas. The graphene-based solid acid catalyst uses a molecular sieve as a carrier, and graphene oxide, WO3 and TiO2 as active components. The key to the present invention is that graphene oxide, WO3 and TiO2 are simultaneously loaded on the molecular sieve carrier as active components, thereby not only significantly improving the desorption efficiency of CO2, but also reducing the desorption energy consumption. In addition, the graphene-based solid acid catalyst provided by the present invention has a strong catalytic ability and a large number of recycling times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of CO2 capture, and specifically relates to a graphene-based solid acid catalyst, a preparation method and application thereof, and a method for treating CO2-containing flue gas. Background Art

[0002] At present, chemical absorption is the most mature application of CO2 capture technology. Among them, organic amine absorption and desorption of CO2 technology has the characteristics of high absorption efficiency and stable operation. This technology adopts the principle of low-temperature absorption and high-temperature desorption. The absorption temperature is usually around 40°C and the desorption temperature is around 100-120°C. The desorption energy consumption is the biggest limitation to the widespread use of this technology. In order to reduce the desorption energy consumption, the total desorption load can be reduced by reducing the rich liquid flow entering the desorption tower, setting up an MVR system for desorption of lean liquid, and diverting part of the rich liquid entering the desorption tower to be heated by the desorption gas at the bottom of the tower, thereby reducing the desorption energy consumption.

[0003] CN106039936A, CN108079746A, CN219043227U, and CN205549971U disclose a CO2 capture method based on a phase-change absorbent. The method uses a series of organic amines and water for compounding to obtain a homogeneous aqueous solution. The solution after absorbing CO2 is automatically stratified, and the upper light phase has no CO2 and directly returns to the absorption tower; the lower heavy phase contains a large amount of CO2 reactants and goes to the desorption tower for desorption. Since the total amount of solution entering the desorption tower is reduced, the desorption energy consumption is reduced. This is a relatively hot method currently studied. Among them, ethanolamine (MEA) has a very fast CO2 absorption capacity, but the desorption energy consumption is as high as 3.7-4.0GJ / tCO2, and it is very corrosive; N-methyldiethanolamine (MDEA) has a fast desorption rate, but the absorption efficiency is limited, and a large amount of circulating liquid is required for absorption, and the equipment investment and floor space are also very large.

[0004] CN114452779A discloses a heat pump assisted phase change carbon dioxide capture system, which uses a combination of an evaporator, a condenser and a compressor based on the phase change carbon dioxide capture method, called a heat pump system, and uses lean liquid after desorption (high temperature 100-120°C), lean liquid before absorption (low temperature about 40°C), rich liquid after absorption (low temperature about 40°C), and rich liquid before desorption (high temperature 80-90°C) for heat exchange, wherein heat medium (heat transfer oil and water) is used for heat transfer, and almost no external heat source is required. Although the patent application takes phase change absorbent as the capture premise, the phase change absorbent can only reduce the desorption flow rate, but cannot reduce the desorption temperature. Since the heat pump uses the phase change heat of the heat medium, the temperature of the heated amine liquid needs to be below the boiling point of the heat medium, so the heat pump system usually needs to be below the boiling point of the heat medium (below 90°C) to be able to operate stably. Summary of the invention

[0005] The first object of the present invention is to provide a graphene-based solid acid catalyst having excellent desorption effect when used to catalyze CO2 desorption.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned graphene-based solid acid catalyst.

[0007] The third object of the present invention is to provide the use of the above-mentioned graphene-based solid acid catalyst as a desorbent for CO2-rich amine liquid.

[0008] The fourth object of the present invention is to provide a method for treating flue gas containing CO2.

[0009] The graphene-based solid acid catalyst provided by the invention uses molecular sieve as a carrier and uses graphene oxide, WO3 and TiO2 as active components.

[0010] The preparation method of the graphene-based solid acid catalyst provided by the present invention comprises the steps of subjecting graphene oxide, a WO3 precursor and a TiO2 precursor to a hydrothermal reaction in a solution, and then mixing the hydrothermal reaction product and a molecular sieve carrier and drying the mixture to obtain the graphene-based solid acid catalyst.

[0011] The method for treating CO2-containing flue gas provided by the present invention comprises the following steps:

[0012] S1. Introduce the flue gas containing CO2 into the absorption tower from the bottom, and spray the CO2 absorbent into the absorption tower from top to bottom. The CO2 in the flue gas reacts with the CO2 absorbent to generate organic salt to remove the CO2 in the flue gas. The bottom of the absorption tower obtains rich amine liquid and the top of the tower obtains the flue gas with CO2 removed;

[0013] S2. Introducing the rich amine solution into a desorption tower for CO2 desorption. The desorption tower uses the above-mentioned graphene-based solid acid catalyst as filler, and the generated CO2 gas is discharged from the top of the desorption tower.

[0014] After in-depth and extensive research, the inventors of the present invention found that molecular sieves have excellent adsorption and catalytic desorption capabilities, and using them as carriers can improve the catalytic ability; graphene is a new type of two-dimensional carbon atomic crystal composed of a single atomic layer of carbon atoms connected by sp2 hybridization, and graphene oxide (Graphene Oxide, referred to as GO) not only contains many reactive carbon-carbon double bonds, but also has a large number of oxygen-containing functional groups, which can easily be surface chemically modified to change its properties. By loading graphene oxide, WO3 and TiO2 as active components on the molecular sieve carrier at the same time, it is possible to simultaneously construct adsorption micro-regions with high affinity between acidic sites and reaction substrates, which can significantly improve the desorption efficiency of CO2. In addition, when the graphene-based solid acid catalyst provided by the present invention is used for CO2 desorption, it can catalyze the high-temperature desorption process, accelerate the CO2 desorption rate, and reduce the desorption temperature to 60-90°C. CO2 desorption can be achieved at this relatively low temperature, which can reduce the desorption energy consumption by more than 30%, and reduce corrosion and pressure because no large amount of water vapor is generated during desorption, thereby reducing the material and cost of the desorption tower. Furthermore, if combined with heat pump technology to meet the desorption requirements, the cost of carbon dioxide desorption technology can be reduced by about 60% to 80%, which plays an important role in promoting the country to achieve the dual carbon goals. In addition, the graphene-based solid acid catalyst provided by the present invention has a strong catalytic ability and can be recycled many times. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the XRD spectrum of graphene-based solid acid catalysts doped with different graphene contents;

[0016] Figure 2 FTIR spectra of graphene-based solid acid catalysts doped with different graphene contents;

[0017] Figure 3 The SEM images of graphene-based solid acid catalysts doped with different graphene contents;

[0018] Figure 4 The XRD patterns of graphene-based solid acid catalysts doped with different TiO2 contents;

[0019] Figure 5 FTIR spectra of graphene-based solid acid catalysts doped with different TiO2 contents;

[0020] Figure 6 The SEM images of graphene-based solid acid catalysts doped with different TiO2 contents;

[0021] Figure 7 is a desorption effect curve diagram of graphene-based solid acid catalyst;

[0022] Figure 8 This is a process flow chart for CO2 capture and desorption. DETAILED DESCRIPTION

[0023] The graphene-based solid acid catalyst provided by the invention uses molecular sieve as a carrier and uses graphene oxide, WO3 and TiO2 as active components.

[0024] In the present invention, the graphene oxide is substantially a hydrophobic nanosheet, and an acidic group and other polar and non-polar groups are bonded to the hydrophobic nanosheet, which can mimic the catalytic characteristics of biological enzymes and construct an adsorption micro-region with high affinity between the acidic site and the reaction substrate. In addition, the graphene oxide has a large specific surface area, can provide a large number of adsorption and reaction active sites, has a planar structure, does not contain micropores that may prevent the reaction substrate from entering, and is conducive to reducing the mass transfer resistance in the catalytic reaction and improving the mass transfer rate.

[0025] In the present invention, based on the total weight of the graphene-based solid acid catalyst, the content of the carrier is preferably 30 to 80 wt%, and the content of the active component is preferably 20 to 70 wt%. Specifically, the content of the carrier can be 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt% or any value therebetween. The content of the active component can be 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt% or any value therebetween.

[0026] In the present invention, the mass ratio of graphene oxide, TiO2 and WO3 in the active components is (1-4): (7-21): 7, at which time the active components can better play a synergistic role and the catalytic CO2 desorption effect is better. Specifically, based on the content of WO3 as 7 parts by weight, the content of graphene oxide is preferably 1-4 parts by weight, such as 1, 2, 3, 4 parts by weight or any value therebetween, and the content of TiO2 is preferably 7-21 parts by weight, such as 7, 8, 9, 10, 12, 15, 18, 20, 21 parts by weight or any value therebetween.

[0027] In the present invention, the molecular sieve can be a ZSM series molecular sieve, a Y-type molecular sieve, an A-type molecular sieve, a T-type molecular sieve, etc., preferably a ZSM series molecular sieve, more preferably H-ZSM-5. The H-ZSM-5 carrier itself has the ability of adsorption and catalytic desorption, and after loading synthesis, the catalytic desorption ability can be further improved.

[0028] The preparation method of the graphene-based solid acid catalyst provided by the present invention comprises the steps of subjecting graphene oxide, a WO3 precursor and a TiO2 precursor to a hydrothermal reaction in a solution, and then mixing the hydrothermal reaction product and a molecular sieve carrier and drying the mixture to obtain the graphene-based solid acid catalyst.

[0029] In a preferred embodiment, the hydrothermal reaction is carried out by ultrasonically dispersing graphene oxide in water, and then mixing the obtained dispersion with organic solvent I to obtain solution A; mixing TiO2 precursor with organic solvent II to obtain solution B; mixing WO3 precursor with organic solvent III to obtain solution C; mixing solution A, solution B and solution C and placing them under hydrothermal reaction conditions for reaction. Wherein, the dispersion time is preferably 2 to 20 hours, such as 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h or any value therebetween. The hydrothermal reaction conditions preferably include a temperature of 120 to 250°C, such as 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 250°C or any value therebetween; the time is 1 to 3d, such as 1d, 1.5d, 2d, 2.5d, 3d or any value therebetween.

[0030] In the present invention, in the specific process of the above-mentioned hydrothermal reaction, the usage ratio of the WO3 precursor, TiO2 precursor, graphene oxide, molecular sieve, organic solvent I, organic solvent II and organic solvent III is preferably (1-5) g: (1-10) mL: (10-150) mL: (3-5) g: (5-50 mL): (5-10) mL: (3-8) mL. Specifically, the usage ratio of the TiO2 precursor to the WO3 precursor can be (1-10) mL:(1-5) g, such as 1 mL:1 g, 2 mL:1 g, 4 mL:1 g, 6 mL:1 g, 8 mL:1 g, 10 mL:1 g, 1 mL:3 g, 2 mL:3 g, 4 mL:3 g, 6 mL:3 g, 8 mL:3 g, 10 mL:3 g, 1 mL:5 g, 2 mL:5 g, 4 mL:5 g, 6 mL:5 g, 8 mL:5 g, 10 mL:5 g or any value therebetween. The usage ratio of the graphene oxide to the WO3 precursor can be (10-150) mL:(1-5) g, such as 10 mL:1 g, 10 mL:3 g, 10 mL:5 g, 30 mL:1 g, 30 mL:3 g, 30 mL:5 g, 50 mL:1 g, 50 mL:3 g, 50 mL:5 g, 80 mL:1 g, 80 mL:3 g, 80 mL:5 g, 100 mL:1 g, 100 mL:3 g, 100 mL:5 g, 120 mL:1 g, 120 mL:3 g, 120 mL:5 g, 140 mL:1 g, 140 mL:3 g, 140 mL:5 g, 150 mL:1 g, 150 mL:3 g, 150 mL:5 g or any value therebetween. The usage ratio of the molecular sieve to the WO3 precursor can be (3-5)g:(1-5)g, such as 3g:1g, 3g:3g, 3g:5g, 4g:1g, 4g:3g, 4g:5g, 5g:1g, 5g:3g, 5g:5g or any value therebetween. The dosage ratio of the organic solvent I to the WO3 precursor can be (5-50mL):(1-5)g, such as 5mL:1g, 5mL:3g, 5mL:5g, 10mL:1g, 10mL:3g, 10mL:5g, 15mL:1g, 15mL:3g, 15mL:5g, 20mL:1g, 20mL:3g, 20mL:5g, 25mL:1g, 25mL:3g, 25mL:5g, 30mL:1g, 30mL:3g, 30mL:5g, 35mL:1g, 35mL:3g, 35mL:5g, 40mL:1g, 40mL:3g, 40mL:5g, 45mL:1g, 45mL:3g, 45mL:5g, 50mL:1g, 50mL:3g, 50mL:5g or any value therebetween.The amount ratio of the organic solvent II to the WO3 precursor can be (5-10) mL: (1-5) g, such as 5 mL: 1 g, 5 mL: 3 g, 5 mL: 4 g, 8 mL: 1 g, 8 mL: 3 g, 8 mL: 4 g, 10 mL: 1 g, 10 mL: 3 g, 10 mL: 4 g or any value therebetween. The amount ratio of the organic solvent III to the WO3 precursor can be (3-8) mL: (1-5) g, such as 3 mL: 1 g, 3 mL: 3 g, 3 mL: 5 g, 5 mL: 1 g, 5 mL: 3 g, 5 mL: 5 g, 8 mL: 1 g, 8 mL: 3 g, 8 mL: 5 g or any value therebetween.

[0031] In the present invention, the WO3 precursor can be an existing compound that can be converted into WO3 after hydrothermal reaction, mixing and drying, preferably tungstate. The tungstate can be sodium tungstate (Na2WO4·2H2O), potassium tungstate (K2WO4·2H2O), ammonium tungstate [(NH4)6WO7O 24 ·6H2O], at least one of calcium tungstate (CaWO4), cobalt tungstate (CoWO4), cadmium tungstate (CdWO4), ferrous tungstate (FeWO4) and zinc tungstate (5ZnO·12WO3).

[0032] In the present invention, the TiO2 precursor can be an existing compound that can be converted into TiO2 after hydrothermal reaction, mixing and drying, preferably a titanate. Specific examples of the titanate include but are not limited to: at least one of tetrabutyl titanate, isopropyl titanate, titanyl sulfate, titanium trichloride and titanium tetrachloride.

[0033] In the present invention, the organic solvent I is preferably a glacial acetic acid solution. The organic solvent II is preferably DMF and / or anhydrous ethanol. The organic solvent III is preferably a hydrochloric acid solution. The terms "I", "II" and "III" are used to distinguish different organic solvents for ease of description and have no other special meanings.

[0034] In the present invention, the drying conditions preferably include a temperature of 50-120°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or any value therebetween.

[0035] The present invention also provides the use of the graphene-based solid acid catalyst as a desorbent for CO2-rich amine liquid.

[0036] like Figure 8 As shown, the method for treating CO2-containing flue gas provided by the present invention comprises the following steps:

[0037] S1. Introduce the flue gas containing CO2 into the absorption tower from the bottom, and spray the CO2 absorbent into the absorption tower from top to bottom. The CO2 in the flue gas reacts with the CO2 absorbent to generate organic salt to remove the CO2 in the flue gas. The bottom of the absorption tower obtains rich amine liquid and the top of the tower obtains the flue gas with CO2 removed;

[0038] S2. Introducing the rich amine solution into a desorption tower for CO2 desorption. The desorption tower uses the above-mentioned graphene-based solid acid catalyst as filler, and the generated CO2 gas is discharged from the top of the desorption tower.

[0039] In the present invention, the CO2 absorbent may be an organic amine, such as at least one of ethanolamine (MEA), N-methyldiethanolamine (MDEA), and the like.

[0040] In the present invention, the CO2 desorption temperature is preferably 80-85°C, such as 80°C, 81°C, 82°C, 83°C, 84°C, 85°C or any value therebetween. In order to control the CO2 desorption temperature within the desired range, it is usually necessary to use a heat exchanger for heat exchange treatment before introducing the rich amine liquid into the desorption tower.

[0041] In the present invention, in order to facilitate the removal of CO2, the absorption tower is generally filled with fillers. The material of the fillers can be at least one of TiO2, WO3, TiO2 / WO3 and TiO2 / WO3 / GO.

[0042] In a specific embodiment, the method for treating CO2-containing flue gas provided by the present invention also includes static stratification of the rich amine liquid before introducing the rich amine liquid into the desorption tower for CO2 desorption, wherein the bottom layer is a CO2-rich solution and the top layer is a CO2-lean solution, the rich CO2 solution is introduced into the desorption tower for CO2 desorption, and the lean CO2 solution is returned to the absorption tower as a CO2 absorbent.

[0043] In a specific embodiment, the method for treating CO2-containing flue gas provided by the present invention further comprises returning the lean amine liquid obtained at the bottom of the desorption tower to the absorption tower as a CO2 absorbent.

[0044] The present invention will be described in detail below through examples.

[0045] Example 1

[0046] The high concentration graphene oxide solution was diluted to 1% (10 mg / mL) with deionized water and then ultrasonically dispersed for 6 hours to obtain a GO dispersion; 37 mL of GO dispersion and 12 mL of glacial acetic acid were stirred and mixed for 30 minutes to obtain solution A; 3.7 g of tetrabutyl titanate and 6 mL of anhydrous ethanol were stirred and mixed to obtain solution B; 3.7 g of sodium tungstate and 7 mL of dilute hydrochloric acid (15%) were stirred and mixed to obtain solution C; solution A, solution B and solution C were stirred and mixed to obtain a hydrothermal reaction, and then placed in an oven and gradually heated to 160°C and maintained for 1 day to complete the hydrothermal reaction. After the reaction was completed, the temperature was cooled to room temperature to obtain a hydrothermal reaction product. The hydrothermal reaction product was mixed with 4.44 g of spherical H-ZSM-5 molecular sieve and then ultrasonically treated, and the obtained ultrasonic treatment product was repeatedly washed and filtered with deionized water, and the obtained solid product was dried at a temperature of 80°C to obtain a graphene-based solid acid catalyst, which was recorded as W1T1-G1.

[0047] The graphene-based solid acid catalyst W1T1-G1 uses H-ZSM-5 molecular sieve as a carrier and graphene oxide, WO3 and TiO2 as active components. The content of the carrier in this catalyst is 53.9wt%, the content of the active component is 46.1wt%, and the mass ratio of graphene oxide, WO3 and TiO2 in the active component is 1:7:7.

[0048] Example 2

[0049] A graphene-based solid acid catalyst was prepared according to the method of Example 1, except that the amount of graphene oxide added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 2:7:7, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T1-G2.

[0050] Example 3

[0051] A graphene-based solid acid catalyst was prepared according to the method of Example 1, except that the amount of graphene oxide added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 4:7:7, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T1-G3.

[0052] Example 4

[0053] A graphene-based solid acid catalyst was prepared according to the method of Example 1, except that the amount of titanium salt added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 1:7:14, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T2-G1.

[0054] Example 5

[0055] A graphene-based solid acid catalyst was prepared according to the method of Example 4, except that the amount of graphene oxide added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 2:7:14, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T2-G2.

[0056] Example 6

[0057] A graphene-based solid acid catalyst was prepared according to the method of Example 4, except that the amount of graphene oxide added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 4:7:14, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T2-G3.

[0058] Example 7

[0059] A graphene-based solid acid catalyst was prepared according to the method of Example 1, except that the amount of titanium salt added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 1:7:21, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T3-G1.

[0060] Example 8

[0061] A graphene-based solid acid catalyst was prepared according to the method of Example 7, except that the amount of graphene oxide added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 2:7:21, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T3-G2.

[0062] Example 9

[0063] A graphene-based solid acid catalyst was prepared according to the method of Example 7, except that the amount of graphene oxide added was changed during the catalyst preparation process so that the mass ratio of graphene oxide, WO3 and TiO2 was 4:7:21, and a graphene-based solid acid catalyst was obtained, which was recorded as W1T3-G3.

[0064] Test Example 1

[0065] W1T1-G1, W1T1-G2 and W1T1-G3 were tested by X-ray diffraction, infrared and field emission scanning electron microscopy (SEM), and the obtained X-ray diffraction spectra, infrared spectra and SEM images are shown in Figure 1 and Figure 2 and Figure 3 .

[0066] from Figure 1It can be seen that the characteristic diffraction peaks of WO3 / TiO2 / GO correspond to tungsten oxide in the standard spectrum (JCPDS card 33-1387) and titanium dioxide in the standard spectrum (JCPDS card 21-1272), respectively. At this time, the peak of graphene has disappeared, which means that graphene has been completely dispersed into a single layer and is no longer in a regularly arranged layer, but is disorderly stacked in space. This proves that the WO3 / TiO2 / GO solid acid catalyst has been successfully prepared.

[0067] Figure 2 The main characteristic peak in the infrared spectrum is shown: 785cm -1 The 1401cm -1 The vibration band of Ti-O-Ti is at 1601cm -1 The absorption peaks near 1040cm can be attributed to Ti-OW bonds; -1 The vibration absorption peak of COC is at 2398cm -1 The weak peak at the bottom is the bending vibration of -OH, which is mainly related to the surface hydroxyl groups and surface adsorbed water of TiO2-WO3.

[0068] Figure 1 and Figure 2 The characterization results showed that the molecular sieve H-ZSM-5 supported WO3 / TiO2 / GO solid acid catalyst had been successfully prepared.

[0069] from Figure 3 It can be seen that WO3 / TiO2 / GO is a three-dimensional block structure formed by the accumulation of nanoparticles. This three-dimensional structure provides more active sites for redox reactions and can shorten the transmission path of reaction particles, thereby showing better catalytic performance.

[0070] Test Example 2

[0071] W1T1-G2, W1T2-G2 and W1T3-G2 were subjected to X-ray diffraction, infrared and SEM detection respectively. The obtained X-ray diffraction spectra, infrared spectra and SEM images are shown in Figure 4 and Figure 5 and Figure 6 .

[0072] from Figure 4 It can be seen that the characteristic diffraction peaks of W1T1-G2, W1T2-G2 and W1T3-G2 also correspond to tungsten oxide in the standard spectrum (JCPDS card 33-1387) and titanium dioxide in the standard spectrum (JCPDS card 21-1272), indicating that changing the mass ratio of tungsten salt and titanium salt can also successfully prepare WO3 / TiO2 / GO solid acid catalyst.

[0073] Figure 5 The main characteristic peak in the infrared spectrum is shown: 1480cm -1 The vibration band of Ti-O-Ti is at 1603cm -1 The absorption peaks near 1041cm -1 is the vibration absorption peak of COC; with the increase of TiO2 content, 2398cm -1 The bending vibration peak of -OH becomes obvious, which indicates that the number of surface hydroxyl groups and surface adsorbed water of TiO2-WO3 increases.

[0074] Figure 4 and Figure 5 The characterization results showed that the molecular sieve H-ZSM-5 supported WO3 / TiO2 / GO solid acid catalyst had been successfully prepared.

[0075] from Figure 6 It can be seen that WO3 / TiO2 / GO is also a three-dimensional block structure formed by the accumulation of nanoparticles. Different mass ratios of tungsten salts and titanium salts will occupy different sites, and the size and degree of accumulation of the catalyst particles formed are partially different.

[0076] Test Example 3 Test Example is used to illustrate the catalytic desorption of CO2-rich amine solvents

[0077] The main body of the intermittent desorption device used in this test example is a three-necked flask with a capacity of 2L. A condensation reflux device is installed in the middle of the bottle mouth to prevent the volatilization of the amine solution. One of the two side bottle mouths is equipped with a thermometer to measure the desorption temperature of the solution, and the other is used for sampling. The three-necked flask uses magnetic stirring to ensure uniform contact between the amine solution and the catalyst.

[0078] A 300 mL volume of the carbon-rich amine solution to be desorbed was added to a three-necked flask, and 3 g of the above catalysts W1T1-G1, W1T1-G2, W1T1-G3, W1T2-G1, W1T2-G2, W1T2-G3, W1T3-G1, W1T3-G2 and W1T3-G3 were added thereto respectively. No catalyst was added to the blank control. The three-necked flask was placed in an oil bath and heated to the required desorption temperature (specifically 80°C), and the desorption process was analyzed by sampling. The CO2 content desorbed by different proportions of catalysts is shown in Figure 2. Figure 7 As shown. Figure 7 It can be seen that, compared with the blank rich amine solution, the use of the WO3 / TiO2 / GO solid acid catalyst provided by the present invention is beneficial to improving the desorption content and desorption rate of CO2.

[0079] Comparative Example 1

[0080] (1) The desorption effects of the best desorption effect catalyst W1T3-G3, the worst desorption effect catalyst W1T2-G2 and the commercial catalyst prepared in the above embodiment were compared. The results are shown in Table 1 below.

[0081] Table 1

[0082]

[0083] It can be seen from the above table that the desorption effect of W1T3-G3 catalyst is better than that of commonly used commercial catalysts.

[0084] (2) The BET specific surface area of ​​the catalyst with the best desorption effect W1T3-G3, the catalyst with the worst desorption effect W1T2-G2 and the commercial catalyst were measured. The results are shown in Table 2 below.

[0085] Table 2

[0086] project <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore ​​size (nm) Commercial Catalysts 128.30 0.219 5.999 <![CDATA[W1T3-G3]]> 157.75 0.465 4.956 <![CDATA[W1T2-G2]]> 129.81 0.221 6.003

[0087] The BET measurement results show that the W1T3-G3 catalyst has the largest specific surface area and pore volume. The larger pore volume and specific surface area may provide more abundant active sites, while the smaller nanoparticle size can reduce the transmission path and diffusion of CO2 and products. The added graphene material can increase the mass transfer rate, accelerate the desorption reaction rate, and improve the utilization rate of the catalyst. Therefore, the WO3 / TiO2 / GO solid acid catalyst prepared by the present invention has a good application effect on the desorption of CO2.

[0088] Application Examples

[0089] The experiment targeted the CO2-rich flue gas generated by a domestic thermal power station and constructed a method for catalytic desorption and carbon capture using graphene solid acid catalyst to recover CO2. The specific process flow chart is as follows: Figure 8 As shown, specifically:

[0090] S1. CO2 flue gas is introduced into the absorption tower from the bottom, and CO2 absorbent (organic amine) is sprayed into the absorption tower from top to bottom. CO2 in the flue gas reacts with the CO2 absorbent to generate organic salt to capture CO2 in the flue gas, thereby obtaining a CO2-rich solution and a CO2-lean flue gas;

[0091] S2. The catalyst W1T1-G2 is fixed in the desorption tower by a thin metal wire, and the CO2-rich solution is heated to 85°C and introduced into the desorption tower, flowing through the catalyst from top to bottom for high-temperature desorption, and the generated CO2 gas is discharged from the top of the desorption tower. The operating data of each process section are shown in Table 3 below.

[0092] Table 3

[0093]

[0094] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. Application of a graphene-based solid acid catalyst as a desorbent for CO2-rich amine liquid, characterized in that: The graphene-based solid acid catalyst uses molecular sieve as a carrier and graphene oxide, WO3 and TiO2 as active components.

2. The use of the graphene-based solid acid catalyst according to claim 1 as a desorbent for CO2-rich amine liquid, characterized in that: Based on the total weight of the graphene-based solid acid catalyst, the content of the carrier is 30-80wt%, and the content of the active component is 20-70wt%.

3. The use of the graphene-based solid acid catalyst according to claim 1 as a desorbent for CO2-rich amine liquid, characterized in that: The mass ratio of graphene oxide, TiO2 and WO3 in the active components is (1-4):(7-21):

7.

4. The use of the graphene-based solid acid catalyst according to claim 1 as a desorbent for CO2-rich amine liquid, characterized in that: The molecular sieve is H-ZSM-5.

5. Use of the graphene-based solid acid catalyst according to any one of claims 1 to 4 as a desorbent for CO2-rich amine liquid, characterized in that: The graphene-based solid acid catalyst is prepared according to the following method: graphene oxide, WO3 precursor and TiO2 precursor are subjected to hydrothermal reaction in a solution, and then the hydrothermal reaction product and a molecular sieve carrier are mixed and dried to obtain the graphene-based solid acid catalyst.

6. The use of the graphene-based solid acid catalyst according to claim 5 as a desorbent for CO2-rich amine liquid, characterized in that: The hydrothermal reaction method is to ultrasonically disperse graphene oxide in water, then mix the obtained dispersion with organic solvent I to obtain solution A; mix TiO2 precursor with organic solvent II to obtain solution B; mix WO3 precursor with organic solvent III to obtain solution C; and mix solution A, solution B and solution C and place them under hydrothermal reaction conditions for reaction.

7. Use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The dispersion time is 2 to 20 hours.

8. The use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The hydrothermal reaction conditions include a temperature of 120-250° C. and a time of 1-3 days.

9. The use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The WO3 precursor is tungstate.

10. The use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The TiO2 precursor is titanate.

11. The use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The organic solvent I is glacial acetic acid solution.

12. The use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The organic solvent II is DMF and / or anhydrous ethanol.

13. Use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The organic solvent III is a hydrochloric acid solution.

14. The use of the graphene-based solid acid catalyst according to claim 6 as a desorbent for CO2-rich amine liquid, characterized in that: The drying conditions include a temperature of 50-120°C.

15. A method for treating flue gas containing CO2, characterized in that: The method comprises the following steps: S1. Introduce the flue gas containing CO2 into the absorption tower from the bottom, and spray the CO2 absorbent into the absorption tower from top to bottom. The CO2 in the flue gas reacts with the CO2 absorbent to generate organic salt to remove the CO2 in the flue gas. The bottom of the absorption tower obtains rich amine liquid and the top of the tower obtains the flue gas with CO2 removed; S2, introducing the rich amine solution into a desorption tower for CO2 desorption, wherein the desorption tower uses a graphene-based solid acid catalyst as filler, and the generated CO2 gas is discharged from the top of the desorption tower; The graphene-based solid acid catalyst uses molecular sieve as a carrier and graphene oxide, WO3 and TiO2 as active components.

16. The method for treating CO2 flue gas according to claim 15, characterized in that: The CO2 absorbent is an organic amine.

17. The method for treating CO2 flue gas according to claim 15, characterized in that: The CO2 desorption temperature is 80-85°C.

18. The method for treating CO2 flue gas according to claim 15, characterized in that: Based on the total weight of the graphene-based solid acid catalyst, the content of the carrier is 30-80wt%, and the content of the active component is 20-70wt%.

19. The method for treating CO2 flue gas according to claim 15, characterized in that: The mass ratio of graphene oxide, TiO2 and WO3 in the active components is (1-4):(7-21):

7.

20. The method for treating CO2 flue gas according to claim 15, characterized in that: The molecular sieve is H-ZSM-5.

21. The method for treating CO2 flue gas according to any one of claims 15 to 20, characterized in that: The graphene-based solid acid catalyst is prepared according to the following method: graphene oxide, WO3 precursor and TiO2 precursor are subjected to hydrothermal reaction in a solution, and then the hydrothermal reaction product and a molecular sieve carrier are mixed and dried to obtain the graphene-based solid acid catalyst.

22. The method for treating CO2 flue gas according to claim 21, characterized in that: The hydrothermal reaction method is to ultrasonically disperse graphene oxide in water, then mix the obtained dispersion with organic solvent I to obtain solution A; mix TiO2 precursor with organic solvent II to obtain solution B; mix WO3 precursor with organic solvent III to obtain solution C; and mix solution A, solution B and solution C and place them under hydrothermal reaction conditions for reaction.

23. The method for treating CO2 flue gas according to claim 22, characterized in that: The dispersion time is 2 to 20 hours.

24. The method for treating CO2 flue gas according to claim 22, characterized in that: The hydrothermal reaction conditions include a temperature of 120-250° C. and a time of 1-3 days.

25. The method for treating CO2 flue gas according to claim 22, characterized in that: The WO3 precursor is tungstate.

26. The method for treating CO2 flue gas according to claim 22, characterized in that: The TiO2 precursor is titanate.

27. The method for treating CO2 flue gas according to claim 22, characterized in that: The organic solvent I is glacial acetic acid solution.

28. The method for treating CO2 flue gas according to claim 22, characterized in that: The organic solvent II is DMF and / or anhydrous ethanol.

29. The method for treating CO2 flue gas according to claim 22, characterized in that: The organic solvent III is a hydrochloric acid solution.

30. The method for treating CO2 flue gas according to claim 22, characterized in that: The drying conditions include a temperature of 50-120°C.

Citation Information

Patent Citations

  • Two-phase amine absorbent for capturing carbon dioxide and application thereof

    CN106039936A

  • CO2 enriched type two-phase absorbent with rapid and spontaneous layering

    CN108079746A

  • Carbon dioxide capture system based on system is absorbed to diphase

    CN205549971U

  • Phase change separation device of phase change absorption liquid and flue gas carbon dioxide trapping system

    CN219043227U